A cross‐scale framework to support a mechanistic understanding and modelling of marine climate‐driven species redistribution, from individuals to communities. Issue 12 (4th August 2020) - Twiname, Samantha; Audzijonyte, Asta; Blanchard, Julia L.; Champion, Curtis; de la Chesnais, Thibaut; Fitzgibbon, Quinn P.; Fogarty, Hannah E.; Hobday, Alistair J.; Kelly, Rachel; Murphy, Kieran J.; Oellermann, Michael; Peinado, Patricia; et al.
Abstract : Climate‐driven species redistribution is pervasive and accelerating, yet the complex mechanisms at play remain poorly understood. The implications of large‐scale species redistribution for natural systems and human societies have resulted in a large number of studies exploring the effects on individual species and ecological communities worldwide. Whilst many studies have investigated discrete components of species redistribution, the integration required for a more complete mechanistic understanding is lacking. In this paper, we provide a framework for synthesising approaches to more robustly understand and predict marine species redistributions. We conceptualise the stages and processes involved in climate‐driven species redistribution at increasing levels of biological organisation, and synthesize the laboratory, field and modelling approaches used to study redistribution related processes at individual, population and community levels. We then summarise links between scales of biological organisation and methodological approaches in a hierarchical framework that represents an integrated mechanistic assessment of climate‐driven species redistributions. In a rapidly expanding field of research, this framework provides direction for: 1) guiding future research, 2) highlighting key knowledge gaps, 3) fostering data exchange and collaboration between disciplines and 4) improving shared capacity to predict and therefore, inform the proactive management of climate impacts on natural systems.